Teachers' Perceptions of Teacher-Centered Learning (TCL) in Learning English at Senior High Schools in Agam Regency - Wahyuni, Nella; Fitrawati, Fitrawati (Journal of English Language Teaching, 2024)
This research was conducted to determine teachers' perceptions of teacher-centered learning and their reasons for using it when learning English. The researcher used descriptive methods with questionnaires and interview instruments to get answers about perceptions and reasons. The sample used in this research to fill out the questionnaire was 20 teachers and interviewed three English teachers in Agam Regency. The researcher provided a questionnaire with 20 statements that teachers had to fill in by choosing answers between strongly agree, agree, disagree, and strongly disagree. After that, the researcher will also interview three teachers. The findings show that teachers have a positive view of teacher-centered learning. In particular, the positivity of the characteristics category statements with seven statements with an average of 3.13, the positivity of the benefits category statements with four statements with an average of 3.20, and the positivity of statements regarding implementation with six statements with an average of 3.13. Meanwhile, the interview results stated that teachers use teacher-centered learning because it makes it easier for them to control the class, focuses students, and facilitates them to convey material in detail. From the results of this research, it can be concluded that teachers still use teacher-centered learning because of the convenience and benefits they experience. Through this research, the findings can help English teachers to be more creative and change teaching techniques to student-centered learning because it is better for students in the 21st century.